ANT22 - Aqueous Emulsion Control Method: Contribution to Rational Control of Dermanyssus Gallinae in Poultry - Aleksandar Pavlićević; Radomir Ratajac; Tamaš Petrović; Aleksandra Tasić; iv Pavlović (Scientific Papers Animal Science and Biotechnologies)
Red poultry mite Dermanyssus gallinae (De Geer, 1778) is an ectoparasite that feeds on the blood of birds and mammals. Invasions of the ectoparasite D. gallinae in intensive poultry farming reach proportions unknown in the wild nature. They are classified as key health, economic, and ecological problems of the most intensive production of foodstuffs of animal origin. Annual losses worldwide are estimated at 3.92 billion USD and tend to grow further. This manifestation of the problem, to a large extent, results from inadequate control of D. gallinae. This study aims to optimize and rationalize the D. gallinae control by external application of inert oils. The ANT 22 method (working name) is based on "know-how" formulation and application technology. In this study, a manual application was carried out in the clinical conditions of 18 small industrial facilities (2,000 - 14,500 animals) of laying hens (cage system), with a total capacity of 151.300 laying hens, in a time frame of 25 months. The effects of D. gallinae control (suppression of infestation) in inhabited and empty non-conditional objects with one treatment lasted 4-10 months, and with two treatments lasted 8-10 months. The observed disadvantages of the method are common to inert oils, which can be minimized with care. The ANT 22 method is safe and does not develop resistance. It is a conditional method, which requires hygienic preparation and adequate application, and is optimal for empty buildings with rest. An important technical condition is the correctness of the applicator and a professionally performed application. Considering the control findings obtained so far, we believe that they justify testing the application of the ANT 22 method for control purposes in large industrial facilities, but also for the purpose of eradicating D. gallinae.